2015
DOI: 10.1148/rg.2015150048
|View full text |Cite
|
Sign up to set email alerts
|

CT of the Abdomen with Reduced Tube Voltage in Adults: A Practical Approach

Abstract: Recent innovations in computed tomographic (CT) hardware and software have allowed implementation of low tube voltage imaging into everyday CT scanning protocols in adults. CT at a low tube voltage setting has many benefits, including (a) radiation dose reduction, which is crucial in young patients and those with chronic medical conditions undergoing serial CT examinations for disease management; and (b) higher contrast enhancement. For the latter, increased attenuation of iodinated contrast material improves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 70 publications
1
51
0
1
Order By: Relevance
“…This potentially reduces the CT dose for the patient or offers a higher contrast‐to‐noise ratio but increases the amount of work while the workflow robustness is decreased by the additional selection of the calibration curves. Other clinics only implement the standard 120 kVp curve for all scans ignoring the potential benefit of a higher signal‐to‐noise ratio or a decreased dose exposure that could be achieved with an optimized tube voltage …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This potentially reduces the CT dose for the patient or offers a higher contrast‐to‐noise ratio but increases the amount of work while the workflow robustness is decreased by the additional selection of the calibration curves. Other clinics only implement the standard 120 kVp curve for all scans ignoring the potential benefit of a higher signal‐to‐noise ratio or a decreased dose exposure that could be achieved with an optimized tube voltage …”
Section: Introductionmentioning
confidence: 99%
“…Other clinics only implement the standard 120 kVp curve for all scans ignoring the potential benefit of a higher signal-to-noise ratio or a decreased dose exposure that could be achieved with an optimized tube voltage. [3][4][5] The commercially available reconstruction algorithm 'DirectDensity' (DD) (Siemens Healthcare, Erlangen, Germany) promises a feasible workflow as it constructs the RED information directly from the raw CT data. 6 DD-CT images obtained this way are independent of the tube voltage once the calibration curve is implemented in the TPS.…”
Section: Introductionmentioning
confidence: 99%
“…However, extremely low tube voltage scans may result in noisier images that are inadequate for interpretation. Increase in tube current or use of IR may improve image quality and lesion conspicuity [26]. Our study showed that the effective dose of 80 kVp CT (2.3 mSv ± 0.9) scan was 45.2% less than 80/Sn150 kVp CT (4.1 mSv ± 1.5) using IR.…”
Section: Discussionmentioning
confidence: 60%
“…Contrastrelated features including enhancement of organs, CNR, and attenuation differences within the tumor border were higher in 80 kVp CT than in 80/Sn150 kVp CT, while SNR showed no significant differences. A potential explanation for these findings is that lowering the CT tube voltage results in a greater photoelectric effect of iodinated contrast media, with only a slight increase in the noise because of improved tube current capabilities; moreover, the advances in hardware equipped with Stellar detectors and software program in third-generation dual-source CT [26,27], which are supposed to be more sensitive to electron influx are thus, dose-efficient and generate high quality images while using 80 kVp. A few studies that investigated DECT, showed that the radiation dose was comparable to the single energy 100-120 kVp CT [14,28].…”
Section: Discussionmentioning
confidence: 99%
“…У відділенні променевої діагностики усім пацієнтам проводили КТ на апараті «Toshiba Aquilion 64» з контрастною речовиною Ультравіст-370, яку вводили внутрішньовенно із розрахунку 1,0-1,5 мл/кг зі швидкістю 4 мл/с. З метою зниження променевого навантаження на пацієнта використовували низькодозові протоколи сканування [16,17].…”
Section: матеріали та методиunclassified